Meaningful Engagement as a Cornerstone for Implementing the Key Recommendations to Advance the Sexual and Reproductive Health and Rights of Women Living With HIV Across Policy, Practice, and Research in Canada - Zoë Osborne MPH; Muluba Habanyama; Brittany Cameron; Alexandra de Pokomandy MD, MSc; Brenda Gagnier; Elizabeth King MD; Jill Koebel MPH; Mona Loutfy MD, MPH; Carrie Martin BA, BSW; Renée Masching MSW; Manjulaa Narasimhan PhD; Valerie Nicholson; et al. (Journal of the International Association of Providers of AIDS Care)
In 2022, a community-academic collaborative team published 5 key recommendations for developing a national action plan to advance the sexual and reproductive health and rights (SRHR) of women living with HIV in Canada. In 2023, a national gathering was convened to strategize implementation of the recommendations across policy, practice, and research settings. Discussions highlighted that meaningful engagement of women living with HIV (recommendation 1) is foundational to implementing the other recommendations. Meaningful engagement requires SRHR stakeholders to: actively dismantle power differentials; commit to engagement as an ongoing process; learn about regionally specific epidemiology and sociostructural forces that create and sustain vulnerability for HIV among women; invest in creating supportive infrastructure; and integrate Equity, Diversity, and Inclusion principles to call diverse groups into the conversation. This Canadian initiative demonstrates how global guidelines can be transformed into nationally tailored action plans to advance the SRHR of women living with HIV, grounded in meaningful engagement.